Kedudukan dan Perlindungan Justice Collaborator pada Sistem Peradilan Pidana - Simanjuntak, Predderics Hockop (JUNCTO: Jurnal Ilmiah Hukum, 2025)
The development of organized crime such as corruption, narcotics, terrorism, and money laundering demands a more adaptive law enforcement strategy, one of which is through the use of justice collaborators. Perpetrators who are willing to cooperate with law enforcement officials have a strategic role in uncovering complex and hidden criminal structures. However, in the Indonesian criminal justice system, the status and legal protection of justice collaborators still face serious problems. This study aims to normatively analyze the position of justice collaborators in Indonesian positive law and evaluate the effectiveness of the legal protection provided to them. The research method used is normative legal research with a statutory and conceptual approach, through an analysis of the Criminal Procedure Code (KUHAP), the Law on Witness and Victim Protection, sectoral regulations, and Supreme Court Circular Letter Number 4 of 2011. The results show that although the existence of justice collaborators has been normatively recognized, its regulations are still partial, unintegrated, and do not provide adequate legal certainty. The absence of explicit regulations in criminal procedural law causes the determination of status and the provision of protection to be highly dependent on the discretion of law enforcement officials and a lack of coordination between institutions. The novelty of this research lies in its positioning of justice collaborators as legal subjects with clear procedural rights and protections, not simply as cooperating perpetrators. This study recommends the need for reform of national criminal procedure law for Justice Collaborators to ensure legal certainty, effective protection, and increased success in eradicating organized crime.